Cues, context, and long-term memory: the role of the retrosplenial cortex in spatial cognition - Miller, Adam M. P.; Vedder, Lindsey C.; Law, L. Matthew; Smith, David M. (Frontiers in Human Neuroscience, 2014)
Spatial navigation requires representations of landmarks and other navigation cues. The retrosplenial cortex (RSC) is anatomically positioned between limbic areas important for memory formation, such as the hippocampus and the anterior thalamus, and cortical regions along the dorsal stream known to contribute importantly to long-term spatial representation, such as the posterior parietal cortex. Damage to the RSC severely impairs allocentric representations of the environment, including the ability to derive navigational information from landmarks. The specific deficits seen in tests of human and rodent navigation suggest that the RSC supports allocentric representation by processing the stable features of the environment and the spatial relationships among them. In addition to spatial cognition, the RSC plays a key role in contextual and episodic memory. The RSC also contributes importantly to the acquisition and consolidation of long-term spatial and contextual memory through its interactions with the hippocampus. Within this framework, the RSC plays a dual role as part of the feedforward network providing sensory and mnemonic input to the hippocampus and as a target of the hippocampal-dependent systems consolidation of long-term memory.